Custom CAD/CAM Peek Implants for Complex Orbitocranial Reconstruction: Our Experience with 15 Patients - Cristina Cárdenas-Serres; F. Almeida-Parra; Anna María Simón-Flors; Patricia de Leyva-Moreno; Álvaro Ranz-Colio; L. Ley; Julio Acero (2024)
Bone defects within the cranio-orbital complex present unique challenges in terms of surgical planning and reconstruction. This article presents a novel approach using PEEK material and advanced surgical technologies to address these challenges. A retrospective analysis of 15 patients who underwent craniofacial reconstruction using patient-specific polyetheretherketone (PEEK) implants between 2016 and 2021 was carried out. Comprehensive preoperative planning was performed, utilizing advanced imaging techniques and specialized software for virtual surgical planning. Patient-specific PEEK PSIs were designed and manufactured based on the preoperative plan. Intraoperative navigation was used to guide the surgical procedure, enabling precise osteotomy and optimal implant placement. This article describes the step-by-step process and the tools utilized in each phase. The etiologies were as follows: meningioma in seven cases, benign lesions in five cases, malignant tumors in two cases, and trauma sequelae in one case. In all cases, 3D-printed PEEK implants were utilized to achieve precise reconstruction. No major complications were described. In one case, an implant replacement was needed with successful outcomes. Our study demonstrates the feasibility and effectiveness of using PEEK patient-specific implants for personalized craniofacial reconstruction. The combination of advanced imaging, virtual planning, and CAD-CAM technology contributes to improved surgical outcomes in terms of oncologic margin control, functional restoration, and aesthetic results.